Overtubes and Foreign Bodies - Norman E Marcon (Canadian Journal of Gastroenterology)
The most common article ingested in adults is food or food products such as nuts, shells, pits and bones. Poorly chewed steak causing bolus obstruction occurs especially in the elderly, while coins are most common in the pediatric group. New techniques of flexible endoscopy have altered and improved management, decreasing the need for surgery. A foreign body in the esophagus mandates prompt removal to avoid perforation. At least 80% of foreign, bodies reaching the stomach pass spontaneously. Once the foreign body is beyond the distal duodenum, it should be followed with serial x-rays. Techniques of removal of meat, bones, shells, bezoars, glass, bottle tops, sharps, pencils, pens, wires, thermometers, gastrostomy tubes, obesity balloons, safety pins, razor blades, button batteries and cocaine packets are described. Complications related to foreign body removal are rare.